Shifting global dynamics: an empirical analysis of BRICS + expansion and its economic, trade, and military implications in the context of the G7 - Logan Cochrane (7822049) (2024)
The 2023 expansion of BRICS (hereafter BRICS+) has resulted in a flurry of journalistic and political narratives. These narratives span a spectrum, between perspectives that emphasize the continuity of the existing global order on the one end and those that note the dawn of a new era and the end of a unipolar world on the other. These discussions have often been based on a limited set of data points, and commonly have not listed the source or limitations of the data used. This paper analyzes the BRICS + and the G7 groups of countries, using long-term empirical data, to assess economic, trade and military metrics. For each domain, multiple metrics are analyzed to validate the extent of change (or lack thereof). The results are compared and contrasted with available narratives. The data shows a notable shift in the global macro-economy, marked by the rise of BRICS + and a relative decline of G7 countries. However, a closer examination of specific economic measures and expected outcomes reveals a more nuanced picture. For trade, BRICS + has a significant share of crucial resources such as oil, gas, and critical minerals, but the G7 continues to maintain a disproportionate share of global goods and services trade, despite experiencing a gradual decline relative to the BRICS + over time. In the realm of military capacities, the G7 countries remain the dominant investor, resulting in technological superiority and military advantage, while the BRICS + have manifold significantly larger military personnel. It is evident that the world is changing, but in more complex and nuanced ways than what is often portrayed, challenging the oversimplified narratives. Other Information Published in: Cogent Social Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311886.2024.2333422